Early severe preeclampsia with marked platelet dysfunction in association with essential thrombocytemia: case report and discussion. Issue 7 (October 2015) - Onisai, Minodora; Voican, Irina; Ciorascu, Mihai; Popov, Viola; Bumbea, Horia; Gaman, Mihaela; Filipescu, Alexandru; Vladareanu, Radu; Vladareanu, Ana-Maria
Abstract : Essential thrombocytemia – a classic myeloproliferative neoplasm characterized by persistent thrombocytosis – may associate both thrombotic and hemorrhagic events, as well as platelet dysfunction. Of all myeloproliferative neoplasms, essential thrombocytemia is more likely to be associated with pregnancy, because of a higher comparative incidence in younger patients. This association significantly increases the risk of pregnancy loss and of various pregnancy complications. We present a case of early severe preeclampsia with a critical and unusual evolution and life-threatening complications.